Changes in acceleration and deceleration capacity throughout professional soccer match-play - Russell, M.; Sparkes, W.; Northeast, J.; Cook, C. J.; Love, T. D.; Bracken, R. M.; Kilduff, L. P. (The Journal of Strength and Conditioning Research, 2016)
As the acceleration and deceleration demands of soccer are currently not well understood, this study aimed to profile markers of acceleration and deceleration capacity during professional soccer match-play. This within-player observational study required reserve team players from a Premier League club to wear 10-Hz Global Positioning System units throughout competitive matches played in the 2013-14 competitive season. Data are presented for players who completed 4 or more games during the season (n = 11), and variables are presented according to six 15-minute intervals (I1-6: 00:00-14:59 minutes, 15:00-29:59 minutes, 30:00-44:59 minutes, 45:00-59:59 minutes, 60:00-74:59 minutes, and 75:00-89:59 minutes, respectively). During I6, the distance covered (total, per minute, and at high intensity), number of sprints, accelerations (total and high intensity), decelerations (total and high intensity), and impacts were reduced compared with I1 (all p = 0.05). The number of high-intensity impacts remained unchanged throughout match-play (p > 0.05). These findings indicate that high-intensity actions and markers of acceleration and deceleration capacity are reduced in the last 15 minutes of the normal duration of match-play. Such information can be used to increase the specificity of training programs designed for soccer players while also giving further insight in to the effects of 90 minutes of soccer-specific exercise. Interventions that seek to maintain the acceleration and deceleration capacity of players throughout the full duration of a soccer match warrant investigation.